Tutor-based approach toward sustainable architecture education - Hassanpour, Badiossadat; Utaberta, Nangkula; Che Ani, Adi Irfan (Elsevier, 2012)
A teaching expert is a valuable asset to any educational institution. These experts are invaluable not only in developing the specific fields of knowledge but also invaluable to other institutions that require their services. Thus, each educator and teacher must strive their utmost to better themselves in their specific field of expertise as well as in other knowledge to reinvent themselves and be able to look at their knowledge in a more meaningful and dynamic fashion and not stick to the same views all the time. But there is tendency to a belief among practitioners that who has some experience in architecture is fully equipped for teaching. This paper discusses the importance of tutor training in architecture education.